885 Surgical Removal of Unerupted Ectopic Maxillary Central Incisors - A Case Report. (12th October 2021) - Mayor, S; McHenry, I
Abstract: Introduction: Maxillary incisors have a significant role on the facial aesthetics of an individual. Following trauma to the primary dentition, the maxillary incisors are vulnerable to eruption failure and occasionally root dilaceration. These teeth can be challenging to treat. Discussion: This case report demonstrates the complex management of a 10-year-old male who presented with severely displaced and unerupted maxillary central incisors, following a history of dental trauma when he was 4 years old. Cone beam computed tomography revealed the upper maxillary central incisors to be lying transversely across the maxillary arch with the crowns directed superiorly and significantly close to the floor of the nose. The incisal edges of both crowns perforated the labial cortex of the maxilla. The roots of the maxillary central incisors were dilacerated with the apices directed superiorly. A multi-disciplinary approach was taken, with involvement from both maxillofacial surgery and orthodontic teams. Maxillofacial surgeons completed the surgical removal of the ectopic maxillary central incisors, rather than the more common approach of surgical exposure and orthodontic repositioning. In this case, full alignment of these teeth would most likely have led to perforation of the labial cortical plate of bone. Conclusions: Although surgery was complex and technique sensitive, both teeth were successfully removed under general anaesthesia with no iatrogenic damage. The patient underwent fixed orthodontics to align the maxillary lateral incisors as central incisors. A multidisciplinary approach along with careful surgical planning and effective communication with the patient and his mother helped to achieve a satisfactory outcome.